The Tradition of Tepuk Tepung Tawar in Malay Weddings from the Perspective of Islamic Law: A Case Study at Tanjungpinang, Riau Islands - Ardiansyah, Ogie; Masrokhin, Masrokhin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Tepuk Tepung Tawar is a ritual in the Malay wedding ceremony, especially in Kampung Melayu of Kota Tanjungpinang Subdistrict. This tradition is also carried out for children who have completed their Qur’an recitation, with prayers for their safety, well-being, and protection from hardship in life. This present study used a sociological method, in which data were analyzed by using the theory of ‘urf (social custom) in Islamic law. Data were collected by means of interview and document study. This study revealed that historically, the tepung tawarceremony for newlyweds would be carried out alternately for each, considering that they have not yet had mahar batih (not yet consummated), while the tepung tawar ceremony for both would be carried out for longtime married couples. The Malay people are very strong in observing their customs and traditions; even giving rise to the Malay proverb “biar mati anak dari pada mati adat”, better for a child to die than for a custom to die. This proverb illustrates how deeply the Malay people are in upholding the customs and traditions of their ancestors. Theoretically, there is also harmony between Islamic law and ‘urf or social custom in Malay weddings.